Are the Informed Consent Forms Applied in the Eye Clinic Enough? - Can, Hümeyra Yıldırım; Yiğit, Yücel; Yüzbaşıoğlu, Erdal (The Bulletin of Legal Medicine, 2022)
Objective: In this study, it was aimed to evaluate the informed consent forms obtained before the surgical procedures performed in the eye clinic. Materials and Methods: Informed consent forms of 300 patients who underwent surgery in the ophthalmology clinic, type of surgery, whether the signature on the consent belongs to the patient, if the signature belongs to someone else, the reason, whether all pages were approved or not, the presence of the patient’s handwritten consent, the signature in terms of who was taken, were retrospectively evaluated. Results: When the consent forms of 300 patients who underwent different surgical procedures were examined, 281 of the signatures belonged to the patients and 19 belonged to someone else. When it was evaluated whether all the pages were signed or not, it was seen that no consent form was signed in accordance with this, and only one page with the patient’s name and signature was signed. The forms were signed by the secretary before the operation on the day of surgery. Conclusion: In our study, informed consent forms were found to be insufficient in many aspects. In order for the physician to protect himself/herself against the risk of a possible medical malpractice claim and to protect the rights of his/her patients, it is important to inform and obtain consent in accordance with ethical and medical procedures.